Patient and physician exposure to X-rays at pediatric interventional cardiology – from world to Poland - Mateusz Mirowski; Joanna Domienik-Andrzejewska; Tomasz Moszura (International Journal of Occupational Medicine and Environmental Health)
Ionizing radiation is considered as a harmful factor to health. However, X‑rays are widely used in diagnostic and therapeutic procedures such as those performed during cardiac interventions. Their use is particularly invaluable in saving life procedures when the risk of adverse effects of radiation is relatively low compared to the consequences of non-treated or treated with other invasive methods diseases. One branch of these types of medical procedures is interventional cardiology in pediatrics due to possible higher than in adults risks of developing cancer in exposed to ionizing radiation children. On the other hand, medical staff in particular physician, may be exposed to relatively high radiation levels during their work. Parallel with enlarging workload (growing number of procedures per year), high levels of cumulative doses to most exposed, and often not protected, parts of operator’s body as eye lenses and brain may be achieved. Exposure to X‑rays in pediatric interventional cardiology is a worldwide point of scientific interest from around 65 years, however assessment and simulating low level doses is still developing. In this review found data presents various trials of evaluating doses or levels of exposure to both medical staff and patient as well as methods of optimization and protection against X‑rays in pediatric cardiac interventional procedures. The issue of establishing diagnostic reference levels was also taken into consideration during analysis. Thirty papers from period 2013 to 2023 were analyzed. The main assumption of this condensed review is to reveal radiation protection methods worldwide and in Poland. Int J Occup Med Environ Health. 2024;37(6):569–80